Harmonizing Hope: An Idea of Music Therapy Interventions for Schizophrenia - Situmorang, Dominikus David Biondi (Buletin Konseling Inovatif, 2025)
Schizophrenia is typified by a wide range of symptoms, such as delusions, hallucinations, cognitive decline, and social disengagement. Even with improvements in pharmaceutical and psychosocial therapy, many people with schizophrenia still require supplementary treatment methods due to their chronic symptoms and functional limitations. Utilizing music's therapeutic capacity to address a variety of symptoms and enhance general well-being, music therapy has emerged as a possible supplementary intervention for schizophrenia. In this study, the author used a literature review with a Critically Appraised Topic (CAT); this research is a summary of the best available evidence regarding the focused aims. This CAT looks at the theoretical underpinnings, empirical data, and therapeutic applications of music therapy for people with schizophrenia. The usefulness of music therapy interventions in regulating attention, affective processing, and social cognition in people with schizophrenia is further supported by psychological and neurological theories. Historical summaries show the major turning points and advancements in the field as they follow the development of music therapy methods and approaches. Following music therapy interventions, there is empirical evidence of decreased positive and negative symptoms, improved psychosocial functioning, and improved quality of life outcomes. The implications for clinical practice also highlight how crucial it is to incorporate evidence-based music therapy interventions into all-encompassing treatment programs for schizophrenia, with a focus on individualized methods, interdisciplinary teamwork, and ongoing professional development. The present research evaluation underscores the diverse advantages of music therapy and its capacity to augment comprehensive treatment and welfare for individuals with schizophrenia.